A Review of the Effects of Ice Accretion on the Structural Behavior of Wind Turbines. Issue 1 (February 2013) - Alsabagh, Abdel Salam Y.; Tiu, William; Xu, Yigeng; Virk, Muhammad S.
Icing of wind turbines happens occasionally at different latitudes and locations in the world and consequently affects the wind turbine fatigue loads. Large ice accretion may cause wind turbine vibration due to uneven ice shedding, which could lead to structural failures in addition to hazardous issues accompanied with ice being shed off wind turbine blades. In this paper, a review study of the effects of ice accretion on the structural behavior of the wind turbines is presented.